Analisis Strategi Pemasaran dalam Membangun Engagement pada Sustainable Experiental Event Promosi Car Free Night Medan - Eni Kusuma Amalia Ningrum; Eryani Eryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the marketing strategies implemented to enhance community engagement within the concept of a sustainable experiential event through the organization of Car Free Night (CFN) Medan as a medium for urban tourism promotion. This research employs a qualitative approach using a case study method focusing on the Kesawan heritage area in Medan City. Data were collected through direct observation, semi-structured interviews, documentation, and literature reviews involving various stakeholders, including event organizers, the Medan City Tourism Office, local MSME actors, creative communities, surrounding residents, and visitors. Data analysis was conducted using the interactive model developed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and conclusion drawing.The findings reveal that CFN Medan’s marketing strategy is implemented through digital promotion, community collaboration, support for local MSMEs, and the enhancement of the Kesawan heritage area as the event’s main attraction. The application of experiential marketing through the dimensions of sense, feel, think, act, and relate successfully creates meaningful experiences for visitors while encouraging active community participation. Furthermore, the sustainable event approach contributes to strengthening the local economy, optimizing the use of public spaces, and enhancing Medan City’s image as an urban tourism destination. This study demonstrates that the integration of experiential marketing and sustainability principles can serve as an effective strategy for fostering community engagement and strengthening Medan City’s branding as a competitive urban destination.